EDUKASI PROBIOTIK SEBAGAI IMMUNOSTIMULANT DAN PENCEGAHAN DYSBIOSIS SERTA OPTIMALISASI POTENSI TUMBUHAN LOKAL SEBAGAI SUMBER PREBIOTIK HABITAT PROBIOTIK - Hasria Alang; Anggraini Putri Utami; Nur Jati Jagad (Jurnal Abdi Negeriku, 2026)
Education about the role of probiotics and the optimization of prebiotics to support probiotics is necessary. Prebiotics are foods or drinks that, when consumed, will improve a person's quality of life. However, due to the perception of partners that probiotics are expensive, and partners' ignorance about the factors supporting probiotic growth, steps are needed to educate partners so they can understand prebiotics and probiotics, which ultimately will improve their health. The purpose of this community service activity is to educate partners about the benefits of probiotics and prebiotics, provide education and examples of probiotic and prebiotic sources that can be obtained from the surrounding environment. The method used is ABCD (Asset-Based Community Development), which utilizes and optimizes the potential of human resources and natural resources. The steps of the PKM activity include preparation, implementation, and evaluation. The results of the intervention showed that this activity increased partners' knowledge from 47% to 95%. This activity also showed high enthusiasm from partners, as seen from active discussions. The results of testimonials showed that partners hope that activities like this can be carried out regularly.